2015
DOI: 10.1177/0030222815572601
|View full text |Cite
|
Sign up to set email alerts
|

This Too Shall Pass

Abstract: Two studies examined African Americans essays on coping with violent and nonviolent death and fading affect bias. Essays from 101 African Americans were coded for psychological resolution (resolved or unresolved) and for type of death (violent or nonviolent). Linguistic analyses were used to examine the experience of loss and coping methods. Religious coping was important for nonviolent death events while social support and emotion (e.g., crying) were themes that emerged for violent death events. For unresolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…However, Teti et al found that Black men who tackled challenges such as racism, incarceration, and unemployment demonstrated resilience amid these stressors (Teti et al, 2012). It has also been found that Black women exhibited resilience in spite of traumatic experiences (Henderson et al, 2015) and in order to cope with depression (Ward et al, 2014). It is this resilience among Blacks that allows this population to thrive and remain optimistic, thus resulting in better mental health outcomes than their counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Teti et al found that Black men who tackled challenges such as racism, incarceration, and unemployment demonstrated resilience amid these stressors (Teti et al, 2012). It has also been found that Black women exhibited resilience in spite of traumatic experiences (Henderson et al, 2015) and in order to cope with depression (Ward et al, 2014). It is this resilience among Blacks that allows this population to thrive and remain optimistic, thus resulting in better mental health outcomes than their counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Across all age cohorts, family satisfaction and contact with friends were found to be the most important contributing factors of general life satisfaction for Blacks (Adams and Jackson, 2000). Black-White differences may be due to culture, which shapes resilience (Keyes, 2009; Teti et al, 2012; Ward et al, 2014; Henderson et al, 2015), body image and perception (Altintas et al, 2014; Coy et al, 2014; Das and Evans, 2014; Stephen and Perera, 2014; Webb et al, 2014b; Laus et al, 2015), and social support (Adams and Jackson, 2000), all influencing mental health. Culture is a powerful influence on health outcomes as described by Kitayama et al in the cultural moderation hypothesis (Park et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Keyes has discussed the “Black advantage” in mental health, possibly due to flourishing in response to adversity [138]. Black–White differences in resilience may be due to culture or previous experience with adversity [40,51,52,139].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the FAB is disrupted by unpleasant emotions, such as dysphoria [3], dispositional mood [22], and trait anxiety [23]. Although FAB research has examined the phenomenon in the context of death [8,24,25], it has not examined the relation of the FAB to grief for death events.…”
Section: Introductionmentioning
confidence: 99%